Strategi Pemberdayaan Masyarakat Desa Wisata melalui Pelatihan Fotografi dan Desain Grafis dalam Optimalisasi Komunikasi Digital - Ahmad Ahsan Ansori (PROGRESIF: Jurnal Dakwah, Sosial, dan Komunikasi, 2025)
The rapid development of the digital era provides significant opportunities for tourist villages to expand their promotional reach through various social media platforms. However, limited digital literacy among local communities often hinders the optimization of digital communication for tourism promotion. This community empowerment program aims to strengthen the capacity of Belik Depok Tourist Village residents through photography and graphic design training as a strategy to enhance digital communication. The implementation methods included needs assessment, practice-based training sessions, content creation mentoring, and evaluation of participants’ visual outputs. The results indicate an improvement in participants’ abilities to capture tourism-related photographs, edit images, and transform them into attractive promotional designs. Furthermore, the community became more capable of independently producing digital content to support tourism marketing across social media platforms. This program contributes to community empowerment and serves as a form of dakwah bil-hal by promoting local economic potential through more effective digital communication.